The Coeur d'Alenes gold rush and it's lasting legacy - Bamonte, Tony, 1942- (Tornado Creek Publications, 2017)
"In the fall of 1883, the announcement of a gold discovery on Prichard Creek ignited a mass hysteria that was typical of western gold rushes...The gold rush is a multifaceted story, laced with excitment, disappointment, success, and failure, and its impact was far-reaching. It was, quite simply, a momentous event that shaped the future of the entire Inland Northwest...The ensuing wealth made the Coeur d' Alenes famous the world over. Spokane, then a struggling outpost in Eastern Washington, became the main outfitting and supply point. Likewise, other communities withing a 100-mile range grew and prospered, and new towns emerged... Simultaneously, the region played remarkable roles in the founding and survival of the U. S. Forest Service, the work of the Civilian Conservation Corps, and a burgeoning logging industry."-- from back cover